Comparative corrosion behavior of titanium alloys (ti-15mo and ti-6al-4v) for dental implants applications: A review - Lopes,Cátia S. D. (2016)
Nowadays there is an increasing need of biocompatible materials due to the toxicity of the metals used. Focusing in dental implants, there are several problems concerning the corrosion of implants, for example, the high concentration of fluoride ions, which make an acid medium. Considering that titanium has excellent biocompatibility and some resistance to corrosion, one way to enhance this property is alloying Ti with other metals. The most used alloy is Ti-6Al-4V, in spite of its toxicity. Hence, there is a need to make new alloys which are resistant to corrosion and less toxic. One that stands out is Ti-15Mo. The objective of this review is to compare these two alloys in terms of corrosion behavior and possible treatments to improve their corrosion resistance.